Changes in Ripening Associated Biochemical and Enzymatic Characteristics of Late Season Mango (Mangifera indica, L.) of Bangladesh - Hossain, M. A. (Journal of Scientific Research, 2016)
Mango is the most important fruit in Bangladesh because of its great utility, characteristic flavor, pleasant aroma and nutritional values, but short shelf life limits its export potentiality to earn foreign currency. To identify the key factors associated with ripening process of late season mango, we comparatively analyzed the unripe (mature green) and ripe fruit of late season mango (Ashwina variety). The starch, reducing sugar (RS), vitamin-C and total titratable acidity (TA) were significantly higher at the unripe stage than that at the ripening stage. The total sugar (TS), non-reducing sugar (NRS), total soluble solid (TSS) and total phenol (PC) were found to be lower at unripe stage than that of the levels of respective parameters at ripen stage. Enzymatic analysis showed that the activity of ?-hexosaminidase increased 13-folds at ripen stage than that at mature stage, while the activity of ?-mannosidase, polyphenol oxidase, ?-galactosidase and ?-glucanase increased moderately; again amylase and invertase activity decreased, suggesting that ?-hexosaminidase is a biomarker enzyme that predominantly associated with the ripening of Ashwina mango.